Reestablishment and a new name for Psidium rufum var. rotundifolium Kiaersk - Tuler, Amélia Carlos; Fonseca, Heitor Lisboa Da; Muniz, Helton Josué Teodoro (Phytotaxa, 2026)
Psidium rufum var. rotundifolium Kiaersk. has recently been treated as a synonym of Psidium rufum Mart. ex DC. Based on the analysis of herbarium specimens, protologues, and original material, we reestablish Psidium rufum var. rotundifolium and propose Psidium verticillatum Tuler as its new name. It is here described, illustrated, and compared morphologically with P. rufum. Psidium verticillatum is distinguished by being predominantly a cespitose subshrub or small tree ranging from 0.5 to 1.5 m tall (vs. tree up to 15 m tall in P. rufum), leaves whorled to oppositely crossed (vs. leaves oppositely), obovate to orbicular elliptic, apex acuminate (vs. elliptical-obovate, apex acute or obtuse) and elliptical fruits, 4-locular (vs. rounded, 3-locular).